2021
DOI: 10.1111/add.15742
|View full text |Cite
|
Sign up to set email alerts
|

Does sex alter the relationship between CYP2B6 variation, hydroxybupropion concentration and bupropion‐aided smoking cessation in African Americans? A moderated mediation analysis

Abstract: Background and Aims CYP2B6, a genetically variable enzyme, converts bupropion to its active metabolite hydroxybupropion. CYP2B6 activity and bupropion‐aided cessation differ between women and men. The aim of this study was to determine whether genetically normal (versus reduced) CYP2B6 activity increases bupropion‐aided cessation in African American smokers via higher hydroxybupropion concentration, and whether this differs by sex. Design and Setting Secondary analysis of a smoking cessation clinical trial (NC… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
3
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 44 publications
(89 reference statements)
0
3
0
Order By: Relevance
“…Three studies used self-reported race to conduct studies exclusively in participants who identified as African American or Black ( Ho et al, 2009 ; Zhu et al, 2012 ; Zhu et al, 2014b ). Two studies used GWAS-based principal components to identify African ancestry (AFR) populations and conduct a single-group association study ( Chenoweth et al, 2018 ; Chenoweth et al, 2022 ). Two studies reflect a homogeneous group of participants without details on race, ethnic, or ancestry measurement-one study with Han Chinese participants and one study conducted in Korea.…”
Section: Resultsmentioning
confidence: 99%
“…Three studies used self-reported race to conduct studies exclusively in participants who identified as African American or Black ( Ho et al, 2009 ; Zhu et al, 2012 ; Zhu et al, 2014b ). Two studies used GWAS-based principal components to identify African ancestry (AFR) populations and conduct a single-group association study ( Chenoweth et al, 2018 ; Chenoweth et al, 2022 ). Two studies reflect a homogeneous group of participants without details on race, ethnic, or ancestry measurement-one study with Han Chinese participants and one study conducted in Korea.…”
Section: Resultsmentioning
confidence: 99%
“…Genetic variants that lead to disease susceptibility or treatment heterogeneity should be identified and differences in variant frequency among ancestry groups determined. Chenoweth et al skillfully employed one approach by employing narrow inclusion criteria (African Americans who smoke ≤ 10 cigarettes/week) and analyzing the effects of common genotypes on bupropion-aided smoking cessation [3] This approach allows for smaller study size to examine if differences in smoking cessation efficacy is due in part to known differences in genetic effects on therapy metabolism.…”
mentioning
confidence: 99%
“…Genetics of smoking can provide information about risk that may increase a individual smoker's motivation and ability to quit, as well as provide genetic information that can be used to increase the effectiveness of pharmacotherapy, as investigrated by Chenoweth et al . [3]. The most important public health significance of understanding the genetic influences of smoking will be in translating that knowledge into improved smoking cessation treatment.…”
mentioning
confidence: 99%